Processes of integration and identity formation in the Roman Republic - Roselaar, Saskia T. (Mnemosyne, Supplements, 2012)
This volume is the result of a conference, held at Manchester in July 2010, on processes of integration and identity formation in the Roman Republic. This book focuses especially on day-to-day contexts in which Romans and Italians interacted, which are essential for understanding long-term developments. The book discusses settlement patterns (e.g. Roman colonies), the Roman army, and the administration of Italy, as well as the long-term consequences of contact, such as growing social and economic networks, linguistic, religious, and cultural changes, transformations of identity in Rome and Italy, and demands for Roman citizenship by Italians. It combines new archaeological evidence with literary and epigraphic evidence, and thus gives an overview of current research on integration and identity in the Roman Republic.